The new media as monitors of democracy - Dumisani Moyo (Communicare)
While Zimbabwe’s first two post-independence elections in 1980 and 1985 were generally considered to be a credible expression of the will of the people, subsequent elections in that country were largely contested, with allegations of rigging, gerrymandering, vote-buying and coercion, among several other irregularities. With a media landscape that is largely dominated by state ownership and control, the total reporting on elections in Zimbabwe has always been openly biased in favour of President Robert Mugabe’s ruling ZANU PF party, resulting in a huge loss of credibility for both the electoral system and the state-owned media themselves. However, the advent of new communications technologies, such as the Internet and mobile phones, has ushered in a new era of political communication where citizens actively participate both in the election campaign and the monitoring processes. This paper looks at the contribution of the innovations in political communication that have come with these new media, focusing particularly on the uses of mobile phones (in particular the SMS or short message service) during Zimbabwe’s contested 2008 election. More specifically, it explores the ways in which ordinary Zimbabweans appropriated the SMS as a tool for monitoring that election. Further, it discusses the implications of these new technologies for the conduct of elections in Zimbabwe and elsewhere on the African continent, and for democracy in general. What is clear is that these new forms of communication are fast eroding the monopoly of incumbent politicians over the communications landscape, undercutting the liberation discourse that has had a stranglehold on election processes, and signalling the possibility of more open political spaces where divergent views can coexist.